Police Favouritism and Crime Reporting in Wukari Local Government Area, Taraba State, Nigeria - Shipurut, Geoffrey Nanbal; Kelvin, Nyikyaa Tersur; Obogo, Okono John (International Journal of Education, Culture, and Society, 2025)
This study investigates the extent to which perceived partiality in policing influences crime reporting behavior among residents of Wukari. A descriptive, cross-sectional survey research design was adopted. From a population of 374,800, a sample size of 400 respondents was determined using the Taro Yamane formula. Questionnaires were distributed to the selected participants through random sampling, and 350 were successfully retrieved for analysis. Data were analyzed using descriptive statistics (frequency, percentages, means, and standard deviations). The findings revealed that the level of crime reporting in Wukari is low. The results also indicated that police favouritism, particularly in favoring wealthy, influential, or famous individuals, has a significant negative impact on crime reporting. Marginalized groups often refrain from reporting crimes due to fear of neglect or retaliation. Statistical analysis showed significant correlations between various dimensions of police favouritism and crime reporting, confirming that favouritism erodes public trust and weakens police-community cooperation. The study recommends that the Nigeria Police Force adopt community-oriented policing strategies to rebuild trust, institutionalize ethics and anti-bias training for officers, and implement transparent accountability mechanisms to ensure equitable treatment of all citizens.